Agroforesty System For Rehabilitation of Degraded Peatland in Central Kalimantan - Marinus Kristiadi Harun; Tri Wira Yuwati (Center for Journal Management and Publication, 2015)
The aim of this research was to analyze the development of jelutung in the agroforestrysystem for the rehabilitation of the degraded peatland fulfilling technically applicable andenvironmentally friendly. Primary data of this research were collected via interviews, observations,field measurements and focus group discussion (FGD) involving all parties. The research resultsshowed that the development of jelutung in agroforestry system was technically applicable, andenvironmentally friendly for the rehabilitation of degraded peatlands. There are 5 certified jelutungseed sources in Central Kalimantan Province that can produce about 126,920,000 seeds per years.The local people’s nursery can produce 1 – 3 million readily planted jelutung seedlings per years. Insallow peatland there are 3 agroforestry systems that have already been developed by the localpeople. In deep peatlands, there are 2 agroforestry systems that have already been developed by thelocal people. Jelutung growth performances on a variety of agroforestry systems showed that theannual stem height increment reached 86.55 – 127.94 cm and stem diameter increased 1.56 – 2.15cm. On the environmental aspect it is known that the diversity of peatland macro-fauna coveredwith jelutung agroforestry was greater than that covered with monoculture and abandoned land (asindicated by Shannon Wiener index values, that were 1.8; 1.,2; 1.7, respectively for PSM method).The peatland covered by jelutung agroforestry exhibited by the following characteristisc: pH=3.94;N total = 0.4%; C organic = 48.58%; C/N = 121.45.